Implementasi Alat Pengusir Burung pada Tanaman Padi Berbasis Panel Surya - Amri, Fauzan; Fitriyanto, Indra; Fatwasauri, Icha (LPPM Universitas Bumigora, 2024)
Indramayu Regency is one of the national rice producers. In increasing the productivity of rice plants, there are many obstacles faced. One of the causes of decreased rice productivity is bird rice pests. Based on the results of the service team's interviews with Jambe Village residents, they experienced crop failure due to bird pests. The aim of this community service is to make a bird repellent device in rice fields based on solar panels. It is hoped that this can overcome the problems in Jambe Village. This activity will start from April to August 2023. The method used is by utilizing sunlight to turn on the equipment. The bird repellent device uses an ultrasonic sensor with a frequency between 25-100 Hz. The ultrasonic sensor will later be turned on using a solar panel which receives power from the sun and then stored in a battery as power storage. From the results of the service, the tool managed to work well and was able to repel rice birds.